Modeling and mapping of contextual factors associated with adolescent birth rates in Thailand between 2009 and 2018 - Thutchanut Phantra; Thanapoom Rattananupong; Kittipong Saejeng; Wiroj Jiamjarasrangsi (BMC Public Health)
Abstract Background To meet indicator 3.7.2 in the Sustainable Development Goals (SDGs), Thailand must reduce the adolescent birth rate (ABR) to below 15 per 1,000 women aged 15–19 years by 2027, down from 20.9 per 1,000 in 2023. Purpose This study aims to describe ABRs geographically, identify hot and cold spots as well as spatial outliers, and determine the association between ABRs and spatial contextual factors at the district level in Thailand from 2009 to 2018. Methods Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR) were employed to examine the spatial patterns of ABRs and the association between ABRs and spatial contextual factors, separately for the 2009–2012 and 2013–2018 periods. Results ABRs at the district level in Thailand during both periods were spatially random. The OLS models for both periods satisfied all OLS requirements, with no correlation issues among explanatory variables (VIF < 5.0). During the 2009–2012 period, five variables were significantly associated with an increase in ABRs: income inequality, annual per capita income, monthly per capita expenses, the percentage of female-led households, and the percentage of households led by a single parent. In the 2013–2018 period, variables associated with an increase in ABRs included income inequality, annual per capita income, the percentage of households affected by divorce, the percentage of adolescents who completed only compulsory level education and were unemployed, and the availability of Youth-Friendly Health Services and safe abortion services. Conclusion As there is no pronounced geographical variation in ABRs and their contextual determinants, a uniform set of policies and programs targeting the reduction of ABRs could be implemented across all districts in Thailand.